Cytokine profiles in pediatric multiple sclerosis. Issue 1 (December 2016) - Bhise, Vikram; Balashov, Konstantin; Sturgill, Marc; Krupp, Lauren; Dhib-Jalbut, Suhayl
Abstract Background The immunopathogenesis of pediatric multiple sclerosis (MS) is not well understood. Methods We studied the cytokine profile in pre-treatment serum specimens of 19 pediatric MS patients, 25 adult MS patients, and 22 age- and gender-matched pediatric healthy controls. In addition to IL-2, IL-12p40, IL-12p70, IL-18, IL-23, IL-6, TNF-α, TGF-β-1, IFN-γ, IL-17A, IL-21, IL-10, IL-4, IL-5, IL-13, and GM-CSF, we measured osteopontin and soluble VCAM-I. Results In children with MS, significantly lower levels of IL-6 were present compared to age- and gender-matched healthy control children (p < 0.05). Moreover, significantly higher levels of osteopontin (p < 0.02) and sVCAM-1 (p < 0.02) and lower levels of IL-6 (p < 0.01) were present, with trends toward lower levels of IL-12p70 (p = 0.074) and IL-17a (p = 0.05) compared to adults with MS. Conclusions These findings indicate important differences in cytokine signatures in children with MS and suggest an unexpected possible lower inflammatory cytokine profile in children with MS.